Intellectual Rent in the Context of the Ecological, Social, and Economic Development of the Agrarian Sector of Economics - YASNOLOB, Ilona; CHAYKA, Tetyana; GORB, Oleg; SHVEDENKO, Pavel; PROTAS, Nadiia; TERESHCHENKO, Ivan (Journal of Environmental Management and Tourism; Vol 8 No 7 (2017): JEMT Volume VIII Issue 7(23) Winter 2017, 2018)
The research of the essence and peculiarities of intellectual rent in the agrarian sector of economics was conducted through the definition of the notions of the sustainable development and intellectual rent. The intellectual rent at four agrarian enterprises during two years was calculated. The impact of the intellectual capital on ecological, social, and economic development in the context of the sustainable development of agrarian sector was determined.